Konsep Al-Ashr dalam Pendidikan Islam - Siregar, Nur Azizah; Suryani, Ira; Pasaribu, Safrina Putri; Bunaiyya, Dila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This journal aims to explore the meaning of surah Al-Ashr (103): 1-3, from this meaning, indications can be obtained that will become the concept of Islamic science. The Prophet as a role model for all Muslims is also the best teacher in the application or practice in accordance with the meaning of surah Al-Ashr. In this surah there are some characteristics of people who include wasting their time for useless things, this has relevance to how the Prophet spent his time by teaching about the knowledge of Islamic Education to his people. Keywords : Al-Ashr, Concept, Islam, Education, Knowledge